2018
DOI: 10.3389/fpsyt.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Functional Neurological Symptoms and Emotion Regulation with Time

Abstract: IntroductionThe present study addressed the variation of emotion regulation in the context of functional neurological symptom disorder (FNSD) by examining changes of functional neurological symptoms (FNS), general psychological strain, alexithymia, emotion regulation strategies, and cortical correlates of emotion regulation in the context of a standard inpatient treatment program.Methods and materialsSelf-report data on FNS, general psychological strain, alexithymia, emotion regulation strategies, and cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
1
4
0
1
Order By: Relevance
“…On the other hand, two studies with functional neurological symptoms, one study with functional dyspepsia and another one with SSD found evidence for an association between reappraisal and SSD: Patients with functional dyspepsia reported less frequent use of positive reappraisal, but more use of rumination and other-blame compared to healthy controls [136]. One study in patients with functional neurological symptoms and another with SSD reported a lower tendency to use cognitive reappraisal compared to healthy controls [100,137]. Similarly, patients with PNES tend to utilize cognitive reappraisal to a lesser extent than controls, which was also associated with cognitive inflexibility [78].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, two studies with functional neurological symptoms, one study with functional dyspepsia and another one with SSD found evidence for an association between reappraisal and SSD: Patients with functional dyspepsia reported less frequent use of positive reappraisal, but more use of rumination and other-blame compared to healthy controls [136]. One study in patients with functional neurological symptoms and another with SSD reported a lower tendency to use cognitive reappraisal compared to healthy controls [100,137]. Similarly, patients with PNES tend to utilize cognitive reappraisal to a lesser extent than controls, which was also associated with cognitive inflexibility [78].…”
Section: Resultsmentioning
confidence: 99%
“… 68 Significant positive associations between severity of dissociation and various psychological features were reported in several samples of FND subtypes, including measures of alexithymia, emotion dysregulation, fearful attachment style and post-traumatic avoidance symptoms. 55 , 75 , 90 , 104 , 117 Other associations included significant positive correlations between dissociation and number of FND symptoms, early onset of FND, in-patient treatment and rates of comorbid psychiatric illnesses. 14 , 45 , 96 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies employed electroencephalography (EEG) to investigate brain connectivity in FND participants. 106 , 117 Xue and colleagues performed EEG with 15 participants with FND-seizures and 15 matched controls; all participants additionally completed the SDQ-20. 106 The FND-seizures group had less linkage between frontal and posterior brain areas relative to controls; no significant associations between clustering coefficients and SDQ-20 scores were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mit Blick auf begleitende Forschungsaktivitäten, aber auch auf die Lehre und die Vermittlung spezifischer Qualifikationen an nachkommende Fachleute aus Psychologie und Funktionstherapien erweisen sich enge Verbindungen zum Lurija-Institut für Rehabilitationswissenschaften und Gesundheitsforschung sowie eine enge Zusammenarbeit mit der Universität Konstanz als hilfreich und produktiv [14]. Forschungsvorhaben und -ergebnisse [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Neben der Behandlung dient es auch der (Weiter-) Entwicklung an den Kontext angepasster Behandlungskonzepte [26]. Begleitende wissenschaftliche Aktivitäten sind im Aufbau, erste Veröffentlichungen erschienen [29][30][31].…”
Section: Modelle Einer Interdisziplinären Versorgungunclassified